Identifikasi dan Penentuan Strategi Pengelolaan Limbah Domestik Pada Kawasan Pesisir Dusun Kisik, Kabupaten Pasuruan - Amanda Cornelia Prastiwi; Firra Rosariawari (Yayasan Literasi Sains Indonesia, 2023)
In Indonesia, around 60% of the total 250 million population lives in coastal areas. Kisik Hamlet is one of the settlements located in the coastal area of the Madura Strait and is a densely populated settlement. The increase in population in coastal areas is vulnerable to increasing problems with the quality of the surrounding waters because people still consider rivers, seas, and beaches as places for dumping solid and liquid waste. In this research, we studied and assessed community perceptions regarding the level of awareness and desire to participate in managing domestic wastewater as an initial idea of whether ongoing research will be conducted regarding wastewater processing facilities in this area. The methods used are observation and interviews, questionnaires, and data analysis with SPSS software. The research results show that the majority of people still dispose of gray water through drainage and directly into the sea, and only a small percentage dispose of black water into septic tanks. However, the level of awareness and desire to participate by the community in waste management efforts is quite high. Therefore, it is necessary to implement a waste management strategy by building a community-based domestic wastewater collection system (Communal IPAL), accompanied by ongoing outreach and education to support the successful implementation and evaluation of this strategy.